2021
DOI: 10.1177/23821205211036836
|View full text |Cite
|
Sign up to set email alerts
|

Educating Future Physicians in Artificial Intelligence (AI): An Integrative Review and Proposed Changes

Abstract: BACKGROUND As medicine and the delivery of healthcare enters the age of Artificial Intelligence (AI), the need for competent human–machine interaction to aid clinical decisions will rise. Medical students need to be sufficiently proficient in AI, its advantages to improve healthcare's expenses, quality, and access. Similarly, students must be educated about the shortfalls of AI such as bias, transparency, and liability. Overlooking a technology that will be transformative for the foreseeable future would place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 88 publications
2
92
0
Order By: Relevance
“…In 2018, the American Medical Association called for “Research regarding the effectiveness of AI instruction in medical education on learning and clinical outcomes” [ 21 ]. Three years later, the available literature suggests UME has been slow to address this call [ 17 ]. Thus, further efforts should be made to advance this original call into practice.…”
Section: A Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, the American Medical Association called for “Research regarding the effectiveness of AI instruction in medical education on learning and clinical outcomes” [ 21 ]. Three years later, the available literature suggests UME has been slow to address this call [ 17 ]. Thus, further efforts should be made to advance this original call into practice.…”
Section: A Methodological Approachmentioning
confidence: 99%
“…Currently, the state of AI in medical education is in its infancy and speculative stages [ 13 - 16 ]. Previously, we have shown that the majority of published literature on the topic call for change in undergraduate medical education and that research is necessary to support curricular changes [ 17 ]. Even so, few have given thought to the steps that must be taken to create this change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these considerations and evidence, we hypothesize that training practitioners can positively affect their attitudes towards adopting AI‐powered technology. However, what exactly practitioners should know about AI to understand the nature of AI, to be able to explain and justify the origin of AI decisions, and to use AI's results in their practice effectively is still an active research area (Grunhut et al, 2021; McCoy et al, 2020). We aim to contribute to this literature with a professional development program (PDP) designed to improve K‐12 teachers' knowledge of AI and trust in AI‐EdTech.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The most recent versions of the Royal Colleges curricula in haematology in the UK or Ireland, for example, do not mention AI in otherwise very comprehensive documents. 4 Although examples of the successful implementation of novel AI-related modules in undergraduate curricula in North America have been described, 5,6 we are not aware of any longitudinal courses in medical AI that span the undergraduate-postgraduate interface in medical specialties, including haematology. We believe that trainees in haematology should have a working knowledge of AI in order to embrace it as a tool for optimising clinical care.…”
Section: W I D E R P E R S P E C T I V E Smentioning
confidence: 99%